2016
DOI: 10.1007/s10694-015-0555-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing a Firefighter’s Immediate Thermal Environment in Live-Fire Training Scenarios

Abstract: Abstract. Detailed characterization of a firefighter's typical thermal exposures during live-fire training and responses can provide important insights into the risks faced and the necessary protections, protocols, and standards required. In order to gather data on representative thermal conditions from a firefighter's continually varying local environment in a live-fire training exercise, a portable heat flux and gas temperature measurement system was created, calibrated, and integrated into firefighter perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 18 publications
(26 reference statements)
4
36
0
1
Order By: Relevance
“…While not a focus of this study, if a firefighter is searching ahead of the line as may be deemed necessary for rescuing a known trapped victim, he/she may experience these high-heat conditions, significantly increasing the risk of equipment failure and burn injury. Extended duration exposure to high heat flux, even in the absence of high ambient temperatures has been shown to be detrimental to firefighting PPE, particularly facepieces that may crack, bubble and deform even if the air temperature is relatively low (Putorti et al 2013;Willi, Horn, and Madrzykowski 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not a focus of this study, if a firefighter is searching ahead of the line as may be deemed necessary for rescuing a known trapped victim, he/she may experience these high-heat conditions, significantly increasing the risk of equipment failure and burn injury. Extended duration exposure to high heat flux, even in the absence of high ambient temperatures has been shown to be detrimental to firefighting PPE, particularly facepieces that may crack, bubble and deform even if the air temperature is relatively low (Putorti et al 2013;Willi, Horn, and Madrzykowski 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The research team supplied all PPE for the participants to enhance standardisation and to ensure that all protective equipment adhered to NFPA standards. been used to characterise risks faced by firefighters in live-fire training scenarios (Willi, Horn, and Madrzykowski 2016) and historically for firefighting activities that were largely exterior focused (Abeles, Delvecchio, and Himel 1973;Gempel and Burgess 1977). However, to date, these data acquisition systems have not been deployed in structure fire scenarios with typical residential fuel packages or linked to data from physiological status monitoring.…”
Section: Participantsmentioning
confidence: 99%
“…Future work should evaluate different combinations of heat flux and cycles, to further characterize the "fatigue" effect of thermal exposures on mechanical properties. These exposures may be able to more accurately match fireground conditions with the recent development of heat flux measuring helmet that has been used to quantify conditions within live fire training structures [28]. In addition, other non-thermal exposure factors should be examined to assess their effect on SCBA lens degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the intensity, duration, and number of exposures to the field worn masks is unknown, and the extreme change in properties may be the result of exposures of a higher intensity, or of a greater number of exposures. Willi et al characterized live-fire training scenarios and found relatively short term exposures to heat fluxes more severe than 5 kW/m 2 [28]. As a quick pilot study, to quantify the effect of single, high-intensity heat exposures on the mechanical properties of the polycarbonate masks, two scenarios were performed on similar masks at a single exposure of 10 kW/m 2 for 90 seconds.…”
Section: Future Potential Investigationsmentioning
confidence: 99%
“…Thermal FED techniques based on air temperature (as measured by thermocouples) do not account for local velocity that can impact heat transfer, nor do they account for the effects of radiant heat. Radiation can have significant impacts on trapped occupants and operating firefighters; for example polycarbonate materials used in firefighting PPE have been shown to soften and damage even when the local air temperature averages 40°C, which was attributed to the significant radiant heat exposure [20]. Alternate FED methodologies exist that utilize heat flux measurements, but common laboratory heat flux gauges are limited when significant moisture is present in the environment.…”
Section: Introductionmentioning
confidence: 99%